Evaluation of the Implementation of Science Subject Teacher Education and Training in Balai Diklat Keagamaan Palembang - Mardianah, Mardianah; Fitria, Happy; Rohana, Rohana (Journal of Social Work and Science Education, 2022)
This study evaluates the quality of education and teacher training at the IPA's Balai Diklat Keagamaan in Palembang. This study employs a qualitative design. The results of the study show that the context program aims to improve people's confidence and skills. However, the process of research is inefficient, therefore the product that is produced does not meet the minimum standards that were expected.